Values of the head loss coefficients of connectors in the press system - Mańko, Robert (Instal, 2022)
The values of the coefficients of local head loss coefficient for straight connectors used in the system with a pressed ring are presented in this paper. Connectors of one of the manufacturers generally available on the Polish market were proposed in the analysis. The paper is limited to three typical and most common sizes. The comparative analysis includes coefficients obtained by direct laboratory measurements, using CFD modeling, analytically using standard 1D formulas and values declared by the manufacturer. Measurements and 3D modeling have shown that the value of the loss factor can be presented as a non-increasing function depending on the average velocity behind the connectors. Significant differences were found between the values of the local loss factors determined in different ways. Taking into account in the calculations the values significantly deviating from the real one may increase or decrease of the flow. Reducing the flow may result in not achieving design parameters. Overdesigning an installation may result in not reaching design parameters, which is created by assuming too large diameters of the conductors, which is ultimately associated with higher material costs. The results presented here can be used as a source of design parameters for designers of pressure installations.